18F-FDG-PET/CT analysis in hospitalized patients affected by pulmonary disease: The experience of the Nuclear Medicine Unit of "Policlinico Tor Vegata". Issue 10 (19th May 2021) - Urbano, Nicoletta; Scimeca, Manuel; Tavolozza, Mario; Bonanno, Elena; Mauriello, Alessandro; Schillaci, Orazio
Abstract : Objective: The main aim of this study was to retrospectively evaluate the clinical data and outcomes of a cohort of 492 hospitalized patients who underwent fluorine-18-fluorodeoxyglucose (F-FDG)-PET/CT analysis at the nuclear medicine unit of 'Policlinico Tor Vergata' in Rome during the years 2017 and 2018 with particular emphasis for patients affected by pulmonary diseases. Methods: Anamnestic data (age and gender), main pathologic conditions, results of F-FDG-PET/CT examination, appropriateness of the request, and medical records of 492 consecutive hospitalized patients who underwent F-FDG-PET/CT analysis (55.38 ± 3.78 years; range 33–81 years) from January 2017 to December 2018 were obtained. Results: Considering all examinations, positive results were observed in 66.9% of cases whereas it was not possible to perform a diagnosis in 12.7% of cases (doubt results). About 20-fold increase in the percentage of doubt results was observed in F-FDG-PET/CT analysis with no appropriateness as compared to those with double appropriateness (both the request and clinical). Noteworthy, our data showed a 95% higher concordance between the positive results of the F-FDG-PET/CT examination and the histologic diagnosis. Conversely, the concordance between the analysis of the bronchoalveolar lavages and the PET analysis was very low. Conclusion: Data here reported showed the high accuracy of the F-FDG-PET/CT performed in our department, mainly for pulmonary diseases, also highlighting the importance of continuously updating the selection criteria for patients who need PET examinations.